Stochastic Model of the Absorption of Drugs Problem in the Cells and Organs - Haddad ALkha, Sajjad Abd-AL Hussein; Khadim, Ihsan (Al-Qadisiyah Journal of Pure Science, 2021)
In this paper we create the stochastic differential equation for the problem of the Absorption of Drugs Problem in the Cells and Organs with fixed volume and then solve this equation and study the stability of the random solution.